Self-repair as indicator for communicative competence: Observation in the speech of L2 undergraduates - Saad, Mohammad Azannee; Zubairi, Ainol Madziah (2020)
One of the primary goals of L2 teaching and learning in the 21st century is for students to develop necessary communicative competence. However, various employment agencies and organisations have raised the concerns over the poor competency in English language among Malaysian students. This study sets out to look into self repair practice as one aspect of communicative competence among undergraduates through a qualitative approach. In particular, this study analyses aspects of speeches that trigger self-repair and subsequently, examines the strategies employed to self-repair. Conversation Analysis was employed as the methodological framework and the guiding principles for the data collection procedure. Participating students were recorded while doing their presentations and/or having consultations with their supervisor. The recording was orthographically transcribed and incidence of self-repair was later identified and coded according to reasons that contribute to its occurrence and strategies for students to restore the disrupted speech. The findings of this research offer insights into resources for language teaching and learning as well as reasons for poor communicative competence among students.